Neovascularization and Pain in Abnormal Patellar Tendons of Active Jumping Athletes - Cook, J. L.; Malliaras, P.; de Luca, J.; Ptasznik, R.; Morris, M. E.; Goldie, P. (Clinical Journal of Sport Medicine, 2004)
Objective: The aim of this study was to investigate tendon pain in abnormal patellar tendons with and without neovascularization. Study design: Comparative design. Setting: Multidisciplinary tendon study group at a competitive volleyball venue. Participants: One hundred eleven volleyball players volunteered to participate in the study. Main Outcome Measures: Subjects' patellar tendons were imaged with ultrasound, with and without Doppler. Tendons that were imaging abnormal were categorized according the presence of tendon neovascularization. Subjects completed 3 pain scales that examined function (Victorian Institute of Sport Assessment score, 100-point maximum), pain with tendon load (decline squat, visual analogue scale, 100-mm maximum), and maximum pain for the previous week (visual analogue scale, 100-mm maximum). A 1-tailed Mann-Whitney U test compared pain scores in abnormal tendons without neovascularization to abnormal tendons with neovascularization. Results: Functional scores were lower (Victorian Institute of Sport score, median, 78; P = 0.045) and pain scores under tendon load were greater (decline squat pain, median, 19; P = 0.048) in subjects with abnormal tendons with neovascularization than subjects with abnormal tendons without neovascularization (Victorian Institute of Sport Assessment score, median, 87; decline squat pain, median, 0). Conclusions: This study indicates that the presence of neovascularization in abnormal patellar tendons is associated with greater tendon pain compared with abnormal tendons without neovascularization in active jumping athletes.